Literature Review: Peran Medium Chain-Triglyceride (MCT) dalam Memperbaiki Profil Lipid pada Kondisi Dislipidemia: Literature Review: The Role of Medium Chain-Triglyceride (MCT) in Improving Lipid Profiles in Dyslipidemia - Tsamaroh Azzah Mukarromah; Berlian Aurelia Amandha; Anggun Rindang Cempaka (Amerta Nutrition, 2023)
Background: Dyslipidemia is a lipid metabolism disorder that causes changes in plasma lipoprotein function and/or levels of Triglycerides (TG), total cholesterol (TC), Low-Density Lipoprotein (LDL), and High-Density Lipoprotein (HDL). Administration of Medium Chain Triglyceride (MCT) is a non-pharmacological therapy that effectively improves lipid profiles and reduces the risk of dyslipidemia. Objectives: This study aimed to conduct a literature study regarding the role of MCTs in improving lipid profiles in dyslipidemic conditions. Discussion: MCT has a role in improving the lipid profile. One food source that contains MCT, which has a role in improving total blood cholesterol, TG, and LDL levels, is Virgin Coconut Oil (VCO). About 60% of MCFA in VCO consists of 52% lauric acid and 12% myristic acid, which can benefit lipid metabolism. In addition, foods containing MCTs have a role in lowering blood cholesterol levels and reducing TG levels. Not only do they play a role in reducing total cholesterol, TG, and LDL levels, but MCTs also increase HDL concentrations. Conclusions: MCTs have a role in improving lipid profiles in dyslipidemic conditions, namely by increasing HDL levels and lowering TG,  total cholesterol, and LDL levels.